An Analytical Study of the Concepts of Peace and Harmony in the Teachings of Samdech Preah Mahäghosananda in Cambodian Society - Ratanarakkhito, Ven Keoratna (Dhammathas Academic Journal, 2015)
The thesis, “An Analytical Study of the Concepts of Peace and Harmony in the Teachings of Samdech Preah Mahāghosananda in Cambodian Society, had three main objectives: (1)to study the life and works of Samdech Preah Mahāghosananda for peace and non-violence in Cambodia,(2) to study Samdech Mahāghosananda’s concepts of peace and harmony in Cambodia, (3) To analyze the concept of peace and harmony of Samdech Preah Mahaghosananda and its influence in Cambodian society. This researchwas based on twomethods: documentary research and fieldwork. The documentary research aimed to study the life and work of Samdech Preah Mahāghosanandaand his teachings on non-violence (ahiósa) by his Dhammayietra or the pilgrimage for peace and reconsolidation for the nation and the world, while fieldwork aimed to study the concepts of his prominent disciples and his genuine supporters by interviewing a few key informants. The findings were presented with the descriptive analysis. The result of the findings clearly indicated that Samdech Preah Mahā Ghosananda was the great Buddhist monk in Cambodia who devoted his whole life to seek peace and harmony for the Cambodian people and the world by absolutely adhering to the Ahiósa Dhamma or non-violence principle. It was clearly found that Cambodia and its people both monks and lay people obtain peace and happiness by following the method of Samdech Ghosananda. It was said that where was Ghosananda, there was no war, no violence, there was presented only cool peaceful mind and authentic well-being only because Samdech Ghosananda was the great political leader of ahimsa as Mahatma Gandhi. The best technique to find peace and harmony of Samdech was Dhammayietra, preaching the simple message of non-violence with its benefits, sharing loving-kindness and compassion, keeping noble silence to be in peace with oneself and be generous to others. Finally, the researcher would conclude from the findings that Samdech Preah Mahāghosananda was the accurate peaceful monk and the peacemaker for Cambodian people and the world. All of his disciples believed in him very faithfully and still regard him as a small Buddha or a spiritual angel in their hearts forever. The thesis, “An Analytical Study of the Concepts of Peace and Harmony in the Teachings of Samdech Preah Mahāghosananda in Cambodian Society, had three main objectives: (1)to study the life and works of Samdech Preah Mahāghosananda for peace and non-violence in Cambodia,(2) to study Samdech Mahāghosananda’s concepts of peace and harmony in Cambodia, (3) To analyze the concept of peace and harmony of Samdech Preah Mahaghosananda and its influence in Cambodian society. This researchwas based on twomethods: documentary research and fieldwork. The documentary research aimed to study the life and work of Samdech Preah Mahāghosanandaand his teachings on non-violence (ahiósa) by his Dhammayietra or the pilgrimage for peace and reconsolidation for the nation and the world, while fieldwork aimed to study the concepts of his prominent disciples and his genuine supporters by interviewing a few key informants. The findings were presented with the descriptive analysis. The result of the findings clearly indicated that Samdech Preah Mahā Ghosananda was the great Buddhist monk in Cambodia who devoted his whole life to seek peace and harmony for the Cambodian people and the world by absolutely adhering to the Ahiósa Dhamma or non-violence principle. It was clearly found that Cambodia and its people both monks and lay people obtain peace and happiness by following the method of Samdech Ghosananda. It was said that where was Ghosananda, there was no war, no violence, there was presented only cool peaceful mind and authentic well-being only because Samdech Ghosananda was the great political leader of ahimsa as Mahatma Gandhi. The best technique to find peace and harmony of Samdech was Dhammayietra, preaching the simple message of non-violence with its benefits, sharing loving-kindness and compassion, keeping noble silence to be in peace with oneself and be generous to others. Finally, the researcher would conclude from the findings that Samdech Preah Mahāghosananda was the accurate peaceful monk and the peacemaker for Cambodian people and the world. All of his disciples believed in him very faithfully and still regard him as a small Buddha or a spiritual angel in their hearts forever.